PELATIHAN AKUNTANSI DAN PENCATATAN TRANSAKSI KEUANGAN PADA UMKM GAPOKTAN SARI MULYO SALATIGA. - Puspita, Maria Entina; Pramono, Joko; Liana, Esther; Dyah, Adelia; Nuraeni, Dwi; Afandi, Rizal; Septiana, Tri; Setiya, Bekti (Fokus ABDIMAS, 2025)
This community service aims to provide accounting and financial transaction recording training to SMEs business actors in the Sari Mulyo Farmers Group (Gapoktan) in Salatiga City. This accounting and financial transaction recording training activity is carried out through presentations, discussions and simulations. The target of this community service activity is for SMEs actors in the Sari Mulyo Farmers Group in Salatiga City. Through this training activity, it is hoped that business actors will be able to manage their cash optimally and start to be disciplined in recording simple bookkeeping that is more organized so that they can record financial transactions simply that supports business decision making. This activity begins by helping SMEs actors identify cash in business needs, training the transaction recording process up to compiling simple cash financial reports. The expected results of this activity are that SMEs actors are able to identify cash and costs in the business, record financial transactions that are more organized and are able to compile their business cash records. The follow-up to this activity is ongoing coaching and mentoring so that the SMEs Gapoktan training participants can truly record financial transactions independently and can compile simple cash reports.Keywords: Accounting Training, Financial Transaction Recording, SMEs Gapoktan Sari Mulyo